Optical emission spectroscopy of 50 Hz pulsed dc nitrogen–hydrogen plasma in the presence of active screen cage. Issue 5 (3rd May 2016) - Saeed, A.; Abrar, M.; Khan, A.W.; Jan, F.; Khan, B.S.; Shah, H.U.; Zaka-ul-Islam, M.; Zakaullah, M.
ABSTRACT: The N2 -H2 plasma gas mixture, generated in a 50 Hz pulsed dc discharge system with active screen cage, is characterized by optical emission spectroscopy (OES), as a function of gas pressure, the fractions of hydrogen and current density. The N2 dissociation degree and N atomic density was measured with actinometery where argon gas is used as actinometer. It was shown that the increase in hydrogen fraction enhances the dissociation of N2, until the maximum of 40%. The excitation temperature is determined from Ar-I emission line intensities by using the simple Boltzmann plot method. The dissociation fraction and excitation temperature is found to increase with hydrogen mixing in nitrogen plasma.